Valorization of nopal wastes to produce quantum dots: optimizing synthesis and exploring in smart textile applications - Mosqueda-Prado, Jesús Baltazar; Pinillos-Bernal, Esteban; Ospina-Montoya, Valentina; Vásquez-Rendón, Mauricio; Forgionny, Angélica; Acelas, Nancy (Frontiers in Materials, 2024)
Quantum carbon dots (QCDs) were efficiently synthesized from post-extraction residues generated during nopal fabric production using a hydrothermal treatment. These QCDs were applied to nopal fabrics, enhancing their UV solar radiation absorption. The synthesized QCDs exhibited fluorescence emissions in the 200-300 nm range. An eco-friendly dispersion was created by incorporating QCDs into TiO2 for use in smart textiles, which underlines our commitment to maintaining a sustainable process. Bright and fluorescent patterns were successfully applied to commercial and nopal fabrics using a spray printing technique. Additionally, the QCDs demonstrated pH-sensitive color changes, paving the way for practical applications. This work represents an initial step towards a circular economy by utilizing residues from nopal fabric production to synthesize quantum dots, which may be employed in smart textiles applications with UV absorption capabilities.